Antibacterial Profile of a Microbicidal Agent Targeting Tyrosine Phosphatases and Redox Thiols, Novel Drug Targets - Kylie White; Gina Nicoletti; Hugh Cornell (MDPI AG, 2021)
The activity profile of a protein tyrosine phosphatase (PTP) inhibitor and redox thiol oxidant, nitropropenyl benzodioxole (NPBD), was investigated across a broad range of bacterial species. In vitro assays assessed inhibitory and lethal activity patterns, the induction of drug variants on long term exposure, the inhibitory interactions of NPBD with antibiotics, and the effect of plasma proteins and redox thiols on activity. A literature review indicates the complexity of PTP and redox signaling and suggests likely metabolic targets. NPBD was broadly bactericidal to pathogens of the skin, respiratory, urogenital and intestinal tracts. It was effective against antibiotic resistant strains and slowly replicating and dormant cells. NPBD did not induce resistant or drug-tolerant phenotypes and showed low cross reactivity with antibiotics in synergy assays. Binding to plasma proteins indicated lowered in-vitro bioavailability and reduction of bactericidal activity in the presence of thiols confirmed the contribution of thiol oxidation and oxidative stress to lethality. This report presents a broad evaluation of the antibacterial effect of PTP inhibition and redox thiol oxidation, illustrates the functional diversity of bacterial PTPs and redox thiols, and supports their consideration as novel targets for antimicrobial drug development. NPBD is a dual mechanism agent with an activity profile which supports consideration of tyrosine phosphatases and bacterial antioxidant systems as promising targets for drug development.